Sistema de copia de seguridad y recuperación de datos en la Casa de la Cultura Ecuatoriana "Benjamín Carrión", Núcleo de Los Ríos. - Vásquez Villanueva, Cristhian Omar (2025)
The following study provides an analysis of the technological infrastructure and data backup policies of the Casa de la Cultura Ecuatoriana Benjamín Carrión, Núcleo de Los Ríos, outlining data management and information security shortcomings. Notably, a lack of automation implementation, reliance on outdated systems, and the scarcity of inter-industry policies and procedures posed a substantial risk of data loss and business operation breaks. The installation of a modern backup system resulted in a 90% decrease in data loss risk, improving overall system’s availability, security, and scalability. Furthermore, advanced encryption protocols, continuous monitoring system, and frequent audits ensured that data integrity and confidentially are maintained. Consequently, there is an opportunity to further strengthen security protocols through regular recovery tests, modernize infrastructure using cloud-based solutions, and implement international policies such as ISO 27001 and TOGAF. Employee training and auditing methodologies may be used to support the longevity and safety of the culture house’s digital backup and preserve institutional heritage.